2023
DOI: 10.1111/jpc.16380
|View full text |Cite
|
Sign up to set email alerts
|

Safety of stimulant medications for attention deficit hyperactivity disorder in paediatric congenital heart disease

Abstract: Aim To review current literature regarding the safety of stimulant medications for treatment of attention deficit hyperactivity disorder in paediatric congenital heart disease (CHD) patients. Methods Embase, MEDLINE complete, CINAHL complete and Psychology and Behavioural Sciences Collection were searched for relevant articles from January 1980 to July 2022. Results One hundred and three articles were identified during the initial search after removal of duplicates. Thirty‐five articles were selected for revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our research methodology is intricately woven around the utilization of diverse datasets, each carefully chosen to address specific facets of our investigative objectives. The Heart Disease UCI dataset [21][22][23][24] serves as a foundational element, standing out with its comprehensive array of 76 attributes that encompass a wide range of patient-related information. From this dataset, we identified a subset of attributes crucial to our analysis.…”
Section: Datasetsmentioning
confidence: 99%
“…Our research methodology is intricately woven around the utilization of diverse datasets, each carefully chosen to address specific facets of our investigative objectives. The Heart Disease UCI dataset [21][22][23][24] serves as a foundational element, standing out with its comprehensive array of 76 attributes that encompass a wide range of patient-related information. From this dataset, we identified a subset of attributes crucial to our analysis.…”
Section: Datasetsmentioning
confidence: 99%
“…11,12 Multiple studies have shown that children with complex medical conditions including congenital heart disease can be safely and effectively treated with stimulant medication. Second, while ADHD medications are highly effective and well tolerated for the majority of patients, including those with congenital heart disease, 13 side effects can outweigh benefit at times and may lead to treatment discontinuation. As this case highlights, it is not known whether susceptibility reflects a specific underlying condition and/or hemodynamic changes induced by a given medication; with a limited formulary clinicians and families will need to carefully weigh the risks and benefits of ADHD medication use for each individual child.…”
Section: Sarah Plummer MDmentioning
confidence: 99%
“…The current study could not explore the risk in this clinical popu-lation. A recent review 9 concluded that stimulants can be safely started in mild congenital cardiac conditions (ventricular septal defect, atrial septal defect, and isolated semilunar valve disease). By contrast, with complex congenital heart disease cases, cardiology opinion is recommended before initiating stimulants.…”
mentioning
confidence: 99%